HUBUNGAN ANTARA PENGALAMAN SEBAGAI KORBAN BULLYING DENGAN PERILAKU SOSIAL SISWA DI PONDOK PESANTREN HIDAYATULLAH TANJUNG MORAWA - Lestari, Dewi; Lubis, Rahmat Rifai; Parianto, Parianto (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This research is motivated by the rampant cases of bullying that occur in educational environments, including pesantren. The purpose of this study was to determine: 1) forms of bullying experiences experienced by students at Pesantren Hidayatullah Tanjung Morawa, 2) social behavior of students who have experienced bullying, and 3) the relationship between experiences as victims of bullying and students' social behavior. This study used a correlational quantitative approach. The study population amounted to 288 students, with a sample of 32 students selected through purposive sampling technique. Data were collected through questionnaires and documentation, and analyzed using the product moment correlation test. The results showed a significant positive relationship between experience as a victim of bullying and students' social behavior with a correlation value of 0.776 and a coefficient of determination of 0.602. This means that 60.2% of social behavior is influenced by the experience of bullying, while 39.8% is influenced by other factors. Common forms of bullying include physical, verbal, and nonverbal. This finding implies the importance of bullying prevention strategies and social behavior coaching in the pesantren environment.